The Effect of Job Training, Competence, and Workload on Employee Performance in the Scrubber Production Process at PT. Feen Marine - Anis Marsela; Muhammad Sidik; Riswandhi Ismail (Penerbit Jurnal Indonesia, 2026)
This study examines the effect of job training, competence, and workload on employee performance in the scrubber production process at PT. Feen Marine. Employee performance is a critical factor in industrial manufacturing environments, particularly in technical production sectors where accuracy, efficiency, and adherence to operational standards determine organizational productivity and product quality. In practice, scrubber production requires employees to possess adequate skills, strong competence, and the ability to manage work demands effectively. Therefore, understanding the determinants of employee performance becomes essential for improving production outcomes and organizational competitiveness. This research employed a quantitative explanatory approach using a cross-sectional survey design. Primary data were collected through structured questionnaires distributed to production employees. The population consisted of 291 employees, and the sample size was determined using the Slovin formula with a 10% margin of error, resulting in 74 respondents. Data analysis was conducted using multiple linear regression with SPSS 26.0, supported by validity and reliability testing, classical assumption tests (normality, multicollinearity, and heteroscedasticity), partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination analysis (R²). The findings indicate that job training has a significant effect on employee performance (Sig. = 0.019), competence also significantly influences performance (Sig. = 0.024), and workload demonstrates a significant impact on employee performance (Sig. = 0.031). Simultaneously, all independent variables collectively affect employee performance, as shown by the F-test significance value of 0.000. The coefficient of determination reveals that 68.4% of employee performance variation is explained by job training, competence, and workload, while the remaining 31.6% is influenced by other factors outside the model. These results suggest that improving employee performance in scrubber production requires an integrated human resource management strategy focusing on effective training programs, competency development, and balanced workload management. This study contributes novelty by providing empirical evidence from a highly technical scrubber production context, which remains limited in previous employee performance research, particularly within marine manufacturing industries.